Social and Demographic Predictors of Consumers' Word of Mouth Engagement in Czechia. Issue 4 (8th August 2021) - Mladenović, Dušan; Bruni, Roberto; Kalia, Prateek
Abstract: Given that consumers' Word of Mouth (WOM) communication is influenced by demographic and social background this study investigates (1) to what extent consumers' WOM engagement is influenced by social relationship variables, (2) in what capacity demographic factors affects preferences to engage in WOM and (3) the preferred WOM environment. Our findings indicate that offline context is preferred, trust and social ties are positively related to WOM, whilst homophily has reportedly negative impact. Age, gender, and education are reported to influence consumers' propensity to engage in WOM. Based on the results, several practical and theoretical implications are discussed.